ANTIMICROBIAL ACTIVITIES OF SOME EUPHORBIA SPECIES - Kirbag, Sevda; Erecevit, Pinar; Zengin, Fikriye; Guvenc, Ayse Nilay (African Networks Ethnomedicines, 2013)
In this study, the antimicrobial activities of methanolic extracts and latex of some Euphorbia species used for medical purposes in Turkey were investigated. The extracts of Euphorbia aleppica L., Euphorbia szovitsii Fisch.&Mey. var. harputensis Aznav. ex M. S. Khan, Euphorbia falcata L. sub. falcata var. falcata, Euphorbia denticulata Lam., Euphorbia macroclada Boiss., Euphorbia cheiradenia Boiss.&Hohen, Euphorbia virgata Waldst.&Kit., Euphorbia petiolata Banks&Sol. were prepared with methanol. The antimicrobial activities of these extracts were examined on test microorganisms as follows: Staphylococcus aureus COWAN 1, Bacillus megaterium DSM 32, Proteus vulgaris FMC 1, Klebsiella pneumonia FMC 5, Escherichia coli ATCC 25922, Pseudomonas aeruginosa DSM 50071, Candida albicans FMC 17, Candida glabrata ATCC 66032, Epidermophyton sp. and Trichophyton sp. by the disc diffusion methods and well agar method. The MIC values of extracts were determined according to the broth microdulitions method. Results indicated that extracts of Euphorbia species inhibited the growth of tested microorganisms in the different ratio. Also, the MIC values of extracts were determined as 31,2-1000 mu g.
Keywords: Antimicrobial activity; Pathogen microorganisms; Medicinal plants